Metabolic responses in Oreochromismossambicus (Peters) exposed towater-accommodated fractions (WAF)of Bombay High Crude Oil - Mathews, Jehosheba P; Philip, Babu (Indian Journal of Fisheries, 2011)
Oreochromis mossambicus (Peters) was exposed to 1.5, 3.0 and 5.0 ppm con-centrations of water-accommodated fractions (WAF) of Bombay High Crudeoil for 21 days and different parameters like total carbohydrate, glycogen, bloodglucose, lactate, pyruvate, lactate dehydrogenase, glycogen phosphorylase ‘a’and glycogen phosphorylase ‘b’ were estimated. A significant dose-dependentchange (P < 0.001) was observed in liver, gill, heart and muscle tissues whichsuggest a severe respiratory stress in the WAF exposed fish and its tendencyof shift in the carbohydrate metabolism more towards anaerobic dependencethan aerobic oxidation.